Inquiry-based learning for science, technology, engineering, and math (STEM) programs a conceptual and practical resource for educators - Blessinger, Patrick; Carfora, John M. (Bingley, U.K. : Emerald, 2015)
Inquiry-based learning (IBL) is a learner-centered active learning environment where deep learning is cultivated by a process of inquiry owned by the learner. It has roots in a constructivist educational philosophy and is oriented around three components: 1) exploration and discovery (e.g. problem-based learning, open meaning-making), 2) authentic investigations using contextualized learning (e.g. field studies, case studies), and 3) research-based approach (e.g. research-based learning, project-based learning). IBL begins with an authentic and contextualized problem scenario where learners identify their own issues and questions and the teacher serves as guide in the learning process. It encourages self-regulated learning because the responsibility is on learners to determine issues and research questions and the resources they need to address them. This way learning occurs across all learning domains. This volume covers many issues and concepts of how IBL can be applied to STEM programs. It serves as a conceptual and practical resource and guide for educators, offering practical examples of IBL in action and diverse strategies on how to implement IBL in different contexts.
Innovative approaches in teaching and learning : an introduction to inquiry-based learning for STEM programs / Patrick Blessinger, John M. Carfora -- Inquiry-based learning in an undergraduate honours program : lessons from the Bachelor of Health Sciences Honours program at McMaster University / Barb Bloemhof -- Two decades of inquiry-oriented learning in first year undergraduate physics laboratories : an Australian experience / Les Kirkup -- Arnold Arons : Pioneer of inquiry-based learning in physics / Richard R. Hake -- MITs Introduction to biological engineering : a longitudinal study of a freshman inquiry-based class / Natalie Kuldell, Rudolph Mitchell -- Problem based learning approaches to teaching chemistry / Dylan Powell Williams -- An intentional and facilitative student-centered approach to enhance inquiry-based learning through authentic, hypothesis-driven research / Amelia J. Ahern-Rindell -- IBL and mathematics : the necessity of flexible knowledge / Vanessa R. Pitts Bannister, Gina J. Mariano -- Advantages of science education outdoors through IBSE methodology / Ana Cristina Tavares, Susana Silva, Teresa Bettencourt -- Inquiry-based learning in action : reflections on an interdisciplinary Master's Program in the Health and Life Sciences / Marjolein B.M. Zweekhorst ... [et al.] -- A narrative-based Bachelor of Science in Nursing Program : experiences and insights / Baiba Zarins, Lorraine Carter -- Modeling scientific inquiry to guide students in the practices of science : the ED3U teaching model of conceptual change in action / Richard E. Shope, William F. McComas -- Utilising context in learning / Wendy Trimmer, Philip Hawes -- Evaluating European inquiry-based education projects through the lens of evaluation capacity building / Fabio Dovigo, Vincenza Rocco -- Inquiry-based learning in mathematics / Mindy Capaldi -- Enhancing inquiry-based learning environments with the power of problem-based learning to teach 21st century learning and skills / Henk Huijser, Megan Y.C.A. Kek, Ruth Terwijn.
Includes indexes.
Print version record
Keywords: Education -- Higher; Higher & further education, tertiary education; Inquiry-based learning; Science -- Study and teaching; Technology -- Study and teaching; Engineering -- Study and teaching; Mathematics -- Study and teaching